2014
DOI: 10.1111/iwj.12294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical incision management on wound infections in a poststernotomy patient population

Abstract: Skin breakdown and infiltration of skin flora are key causative elements in poststernotomy wound infections. We hypothesised that surgical incision management (SIM) using negative pressure wound therapy over closed surgical incisions for 6-7 days would reduce wound infections in a comprehensive poststernotomy patient population. 'All comers' undergoing median sternotomy at our institution were analysed prospectively from 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 9 publications
1
86
0
Order By: Relevance
“…Under the designation closed incision negative pressure therapy (ciNPT), this new technique has resulted in many significant clinical results (11,13,25,26). Since 2010, multiple studies and case reports comparing standard-of-care dressings to ciNPT have reported a decrease in SSIs in a wide spectrum of traumatic, orthopaedic, abdominal, sternal and plastic surgery incisions (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The reason for this success may be due to the reported mechanisms of action of the ciNPT, which protects the incision from external wound contamination, strengthens the cohesiveness of the wound edges, removes fluids and infectious materials from the wound, decreases the lateral tension around the incision and facilitates oxygen saturation and blood microcirculation within the incision area (11,38,39).…”
Section: Key Messagesmentioning
confidence: 99%
“…Under the designation closed incision negative pressure therapy (ciNPT), this new technique has resulted in many significant clinical results (11,13,25,26). Since 2010, multiple studies and case reports comparing standard-of-care dressings to ciNPT have reported a decrease in SSIs in a wide spectrum of traumatic, orthopaedic, abdominal, sternal and plastic surgery incisions (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The reason for this success may be due to the reported mechanisms of action of the ciNPT, which protects the incision from external wound contamination, strengthens the cohesiveness of the wound edges, removes fluids and infectious materials from the wound, decreases the lateral tension around the incision and facilitates oxygen saturation and blood microcirculation within the incision area (11,38,39).…”
Section: Key Messagesmentioning
confidence: 99%
“…It delivers intermittent or continuous negative pressure (ranging from <50mmHg to >125mmHg) to the wound site which is covered with a foam or gauze dressing and sealed with an occlusive drape. Success has been reported in complex wounds 35 with emerging evidence to show that its use in high risk, post-operative incisions prevents SSIs [36][37][38][39][40] . The likely modes of action are through holding wound edges together (thereby reducing the likelihood of surgical dehiscence), stimulation of perfusion, reduction of lateral tension, haematoma and oedema, and protection of the surgical site from exogenous sources of micro-organisms.…”
Section: Negative Pressure Wound Therapy (Npwt)mentioning
confidence: 99%
“…Grauhan et al [111] showed significant reduction of SSIs in obese patients (body mass index > 30 kg/m 2 ) with median sternotomy compared with patients treated with standard wound dressings. In general, retrospective studies and randomized controlled trials provided a substantial body of evidence that the use of this prophylactic wound dressing technique may reduce the incidence of wound infections [112][113][114] . …”
mentioning
confidence: 99%